Kajian filologi dan cara mendidik dalam naskah Dhedhasaraning Wewatekanipun Manungsa - Arini, Bunga Candra Nur; Nurhayati, Endang (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2020)
This research aims to reveal the steps of philology research on the Dhedhasaraning Wewatekanipun Manungsa text and reveal how the text can be used by teachers to educate students with different personalities, so learning can be more effective. This study is qualitative research utilizing philological approach. The data were analyzed using content analysis techniques, starting from unitization, sampling, recording data, describing data, making inferences, and analyzing data. The results of this study include manuscript inventory, manuscript description, transliteration, and editing of the Dhedhasaraning Wewatekanipun Manungsa manuscript. The study also discusses the manuscript proposes ways to educate students based on their personalities, for example, bingahan personality students are educated with an enthusiastic approach, kerasan personality students are educated in a decisive style, sedhihan personality students are educated with understanding and encouragement, while sarehan personality students are educated patiently. The Dhedhasaring Wewatakipun Manungsa text contains values that could be a guide for teachers to educate their student according to their personalities, make teaching and learning more effective, and developing students’ characters.